2022
DOI: 10.1021/acs.langmuir.2c02463
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating SERS Sensitivity for Pesticide Malathion Detection with Synergistic Boosting Effect by Hydrogen Cations and Chloride Anions

Abstract: Although SERS has been widely recognized as one of the highly sensitive analytical methods that can be deployed in the field with high sensitivity and short analysis time, reports regarding the fast determination of malathion at low concentrations are still scarce. Here, in this work, the solution pH and various halogen co-adsorbates were explored to promote the SERS signal of malathion using the citratereduced Ag NPs. It was found that chloride anions were the most efficient signal booster among the three hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
(66 reference statements)
1
4
0
Order By: Relevance
“…It was suggested that halide ions can enhance the SERS signal by forming a coating layer over the Ag NPs upon ligand exchanges. As shown in Figure S2 , the largest red shift of UV spectra was caused by iodide ion, which further confirmed that the optimum halide ion species is generally target specific [ 24 , 27 ].…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…It was suggested that halide ions can enhance the SERS signal by forming a coating layer over the Ag NPs upon ligand exchanges. As shown in Figure S2 , the largest red shift of UV spectra was caused by iodide ion, which further confirmed that the optimum halide ion species is generally target specific [ 24 , 27 ].…”
Section: Resultssupporting
confidence: 56%
“…Among them, certain inorganic salts showed considerable signal enhancing efficiency. Halide ions were considered effective co-adsorbates to enhance the SERS sensitivity, and many groups, including us [ 24 , 25 ], had been working in this field intensively. For example, polycyclic aromatic hydrocarbons [ 26 ], antibiotics [ 27 ], drugs [ 28 ] have been shown to enhanced SERS signals in the presence of certain halogen ions.…”
Section: Introductionmentioning
confidence: 99%
“…As demonstrated by Kim et al, tuning the surface adsorption on SERS substrates could bring higher dimensionality, thus, better differentiation. Since halogen ions have been widely shown the potential for coadsorption of certain chemicals, , three halogen ions (Br – , I – , and Cl – ) were screened. As shown in Figure S2, after mixing with 10 mM of the halogenate potassium salt (KBr, KI, KCl), all the normalized absorption spectra of Ag-NPs showed red shift, which was consistent with previous reports and proved the successful modification of Ag-NPs by halogens.…”
Section: Resultsmentioning
confidence: 99%
“…Since halogen ions have been widely shown the potential for coadsorption of certain chemicals, , three halogen ions (Br – , I – , and Cl – ) were screened. As shown in Figure S2, after mixing with 10 mM of the halogenate potassium salt (KBr, KI, KCl), all the normalized absorption spectra of Ag-NPs showed red shift, which was consistent with previous reports and proved the successful modification of Ag-NPs by halogens. As shown in Figure S4a,b, the introduction of Br – ion not only greatly enhanced the SERS signal of LL but also brought much more SERS features, notably at 620, 934, 1034, 1108, 1270, and 1379 cm –1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation